91 Maternal Programming of the Piglet Microbiome from Birth to Weaning. (7th May 2021) - Law, Kayla; Lozinski, Brigit; Torres, Ivanellis; Hillbrands, Adrienne; Nelson, Emma; Johnston, Lee; Gomez, Andres
Abstract: The objective of this study was to investigate seeding of the piglet microbiome, in the context of maternal programming in pre/perinatal environments. Maternal programming refers to maternal factors that predetermine offspring development and health. We hypothesized that increased sanitation level in maternal environments affects development of piglet fecal and nasal microbiomes, and physiological performance. Six sows were allocated randomly to two treatment groups: farrowing stalls cleaned with (D; n = 3) or without (ND; n = 3) disinfectant. Swabs were collected from stall floors, drinkers and feeders, and from sows' vaginal, rectal, oral and udder surfaces at d109 of gestation and the day before farrowing. Fecal and nasal swabs were collected from piglets at days: 0 (within 24h of birth), 7, 14, and 21 postpartum. Nine piglets were selected randomly from each sow (n = 27/treatment) for microbiome analyses. DNA was extracted from swabs and the V4 variable region of the 16srRNA bacterial gene was sequenced on the MiSeq platform. Sequence data were analyzed using DADA2 and various packages within the R statistical software. Although environmental microbiomes were different between D and ND stalls (PERMANOVA, R2=0.474, P = 0.031) after cleaning, no compositional differences were detected among any D or ND sow samples. However, at d0, ND compared with D piglets exhibited higher gut (Shannon's H, P = 9.131e-08) and nasal (P = 6.164e-08) alpha diversity. ND piglets also displayed greater nasal bacterial diversity at d21 (P = 0.036), and different gut (R2=0.06–0.129, P = 0.001) and nasal (R2=0.136–0.196, P = 0.001) microbiome compositions across all timepoints. However, D piglets exhibited higher average birth (P = 3.773e-05) and weaning weights (P = 5.803e-06) compared to ND piglets. These results indicate that sanitation level during farrowing persistently alters swine microbiomes and growth performance.